The Exercise of Power and Its Resistance in Isle of Dogs - Gracia Veva (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study attempts to show the forms of power exercised by a government and the resistance by the powerless in Isle of Dogs. In this study, I focus on power relations between the government led by Mayor Kobayashi and the powerless party which are the people and dogs. I address two problems which are the way the government exercises power and the way the powerless resists it. I use Foucauldian power relations and the concept of propaganda by Michel Sproule to help me analyze the problems. From the analysis, I find that power is exercised by the subjects who are able to manipulate others from their strategic position. I also found that power is fluid, and it transforms as it faces struggle and resistance. Finally, I find that in the field of power relations in a democratic society, people have a big role in determining the form and strength of the power that circulates in that society. Keywords: Power, Resistance, Strategy, Democracy, Obedience.